Composição florística e estrutura fitossociológica de uma floresta estacional semidecidual em Araras, SP - Soares, Marcelo Steinmetz (2007)
The purpose of this study was to analyze the specific composition of tree, arboreal structure, infestation by climbers, canopy layer and compare the results with other forest fragments and, from these, to form a data bank for monitoring. The forest studied is located in the geographical coordinates S 22º 17 and W 47º 24 . The soil is red-dark Latosoil type and its topography is irregular. The floristic analysis was made by expeditions and phytosociology by quadrats of 10x10m in three blocks. The canopy analysis was made by digital image and the climbers infest by coverage index. It was found 114 species belonging to 40 families and 74 genres. It was sampled 728 alive plants. The species with greater importance value were Trichilia clausenii, Galesia integrifolia, Trichilia catigua, Metrodora nigra e Cariniana estrelensis. The sample canopy coverture presented 70% of the samples with 70% of coverture e only 14% with minor than 50%. 83% of the trees presented any infestation by climber and 60% with indice 4 e 5, that was considered elevated. The greatest infestation occurred at the tree of the canopy layer. The population of pioneer species, in the sucessional classification, presented little number of young plants and the secondary and shade tolerant great number and a complete series of diametric classes.